2018
DOI: 10.18823/asiatefl.2018.15.4.8.1005
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Teachers through Core Reflection : A Case in Korea

Abstract: This study explored the reflection process of secondary in-service English teachers during a graduate course. In particular, the study aimed to examine the type of reflection the teachers are engaged in as they strive toward experiencing core reflection. In addition, the restricting and contributing factors during the process of reflection were also looked into. A total of 17 in-service secondary English teachers participated in this study. The data were collected from class observations, group discussions, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This "reinterpreting" task can help the pre-service teachers to go through the necessary process to reflect on how to transform ESL theories for the EFL context. The process may include becoming aware of the gaps in their understanding of the theories and methods as well as questioning their knowledge of the current demands in the national curriculum (Yin 2018). This reflection can allow the pre-service teachers to gain a deeper understanding of the concepts in addition to evaluating their applicability in the EFL classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…This "reinterpreting" task can help the pre-service teachers to go through the necessary process to reflect on how to transform ESL theories for the EFL context. The process may include becoming aware of the gaps in their understanding of the theories and methods as well as questioning their knowledge of the current demands in the national curriculum (Yin 2018). This reflection can allow the pre-service teachers to gain a deeper understanding of the concepts in addition to evaluating their applicability in the EFL classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…Kiral, 2020;Melenyzer, 1990, Short, 1992Wilcoxen et al, 2019). There are also literature review studies (Akcakaya, 2004;Conger & Kanungo, 1988;Foster, 1990;Kiral, 2019;Thomas & Velthouse, 1990); however, there have been few qualitative studies on teacher empowerment (Cetin & Kiral, 2018;Yin, 2018). For this reason, it is thought that this study will provide a profound perspective to the literature in the light of its qualitative findings and will guide school principals.…”
Section: Empowerment Processmentioning
confidence: 95%
“…Most of the quantitative studies are found in the literature on teacher empowerment (Avidov-Ungar & Arviv-Elyashiv, 2018; Celik & Konan, 2020;Ganiban et al, 2019;Kiral, 2020;Melenyzer, 1990, Short, 1992Wilcoxen et al, 2019). However, limited studies conducted on teacher empowerment by using qualitative research design in the literature (Cetin & Kiral, 2018;Yin, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%